The impact of disasters on international trade - Martin Gassebner; Alexander Keck; Robert Teh (World Trade Organization (WTO), 2006)
In this paper we examine the impact of major disasters on international trade flows using a gravity model. Our panel data consists of more than 170 countries for the years 1962-2004 yielding approximately 300,000 observations. We find that the driving forces determining the impact of such events are the democracy level and, to a lesser extent, the area of the affected country. The less democratic and the smaller a country the more are its trade flows reduced in case it is struck by a disaster. We are also able to distinguish between the effect of a disaster on an importing and an exporting country.
Keywords: F14; P52; P48; C23; 330; International trade; disasters; gravity model; Außenwirtschaft; Naturkatastrophe; Gravitationsmodell; Welt